Asuhan Keperawatan Jiwa Pada Tn.S Dengan Gangguan Isolasi Sosial: Menarik Diri Di Ruang Arjuna RSJ Daerah Surakarta - Hermawan, Beny; , Agus Sudaryanto, S.Kep., Ns., M.Kes (2015)
Background : Social isolation found in Surakarta Regional Mental has increased from year to year with the cause of the difficulty one faces the pressures of life, low education and low socioeconomic condicions. Aim of Research : To study about nursing care on clients with social isolation withdray include assessment, intervention, implementation and evaluation. Result : After implementation of nursing care 3x24 hour it found that the client is able to recognize the results obtained causes social isolation, gains and losses relating to relate to others, how to get acguainted, acguainted with the nurse, but not yet able to get acguinted with other clients to the fulles. Conclusion : Team work between care giver and clien/family absolutly needed for success on nursing care, therapeutic communication was encourage more cooperative clients, optimum utilization of time and family support is very important roles in the nursing process with clients withdrawing social isolation. Key Words : Social isolation, Withdraw, Nursing care.